Cell and molecular biology : concepts and experiments - Karp, Gerald (John Wiley & Sons, 2008)
Using sample experiments to support the underlying concepts, this textbook introduces students to the scientific methods and processes concerned with cellular and molecular biology. Narratives at the end of each chapter describe some of the key experimental findings of recent years.